2019
DOI: 10.1016/j.tics.2019.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Object Vision in a Structured World

Abstract: In natural vision, objects appear at typical locations, both with respect to visual space (e.g., an airplane in the upper part of a scene) and other objects (e.g., a lamp above a table ). Recent studies have shown that object vision is strongly adapted to such positional regularities. In this review we synthesize these developments, highlighting that adaptations to positional regularities facilitate object detection and recognition, and sharpen the representations of objects in visual cortex. These effects are… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
136
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 150 publications
(149 citation statements)
references
References 134 publications
13
136
0
Order By: Relevance
“…Focusing on the interplay of multiple scene elements, the current study shows that on higher levels of the scene processing hierarchy, the visual system uses spatial regularities to concurrently process the multiple elements of complex scenes in an efficient way. This result is in line with the emerging view that real-world structure facilitates processing in the visual system across diverse naturalistic contents (Kaiser, Quek, Cichy, & Peelen, 2019).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Focusing on the interplay of multiple scene elements, the current study shows that on higher levels of the scene processing hierarchy, the visual system uses spatial regularities to concurrently process the multiple elements of complex scenes in an efficient way. This result is in line with the emerging view that real-world structure facilitates processing in the visual system across diverse naturalistic contents (Kaiser, Quek, Cichy, & Peelen, 2019).…”
Section: Discussionsupporting
confidence: 89%
“…A major reason for this perceptual efficiency lies in the structure of natural scenes: for instance, a scene's spatial structure tells us where specific objects can be found and its categorical structure tells us which objects are typically encountered within the scene (Kaiser, Quek, Cichy, & Peelen, 2019;Oliva & Torralba, 2007;Võ, Boettcher, & Draschkow, 2019;Wolfe, Võ, Evans, & Greene, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The early facilitation of category information is consistent with results from single-object processing, where representations of individual objects are rapidly enhanced -within the first 150ms of vision -when the objects appear in their typical real-world locations, such as an eye in the upper visual field (Issa & DiCarlo, 2012) or a shoe in the lower visual field . Together, these findings therefore support the idea that real-world structure can boost basic visual analysis across diverse stimuli and processing levels (Kaiser et al, 2019a).…”
Section: Discussionsupporting
confidence: 71%
“…In everyday situations, the input to our visual system is not random. It rather arises from structured scenes, in which information follows meaningful distributions across space (Bar 2004;Kaiser et al, 2019a;Oliva & Torralba, 2007;Võ et al, 2019;Wolfe et al, 2011). Neuroimaging studies have shown that the visual system is sensitive to this structure, with cortical responses differing when scene elements do or do not adhere to typical real-world structure (Abassi & Papeo, 2019;Baldassano et al, 2017;Bilalic et al, 2019;Kaiser et al, 2014;2019b;Kaiser & Peelen, 2018;Kim & Biederman, 2011;Roberts & Humphreys, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…One open question is whether visual cortex contains representations that reflect the natural statistics of object locations in images. Here we examined object co-occurrence independent of object location, but it is known that the visual system also takes advantage of associations between objects and spatial locations 60 and that perceptual behaviors and cortical representations are sensitive to violations of the typical positions of objects 2,61-63 . Future investigations could utilize annotated image databases to explicitly quantify these spatial statistics and to examine how they relate to the object representations of visual cortex.…”
Section: Natural Statistics and Cortical Representationmentioning
confidence: 99%